1982
DOI: 10.1557/proc-15-777
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Measurements in Concrete and Compacted Bentonite

Abstract: A laboratory method for measurement of diffusion of radionuclides inconcretes and compacted bentonite has been developed. In this method a tracer is introduced through one end into the cylindrical sample closed in a tube and preequilibrated with water. After the introduction period of the tracer the tube is sealed hermetically and the concentration profiles of the radionuclides are measured periodically from the outside of the sample using a collimated detector. Diffusivities are calculated from the activity p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
1999
1999

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…It was indicated that significant constriction and tortuosity were resulted. However, the iodide ion diffusion in the interstitial water at a steady-state flux NA can be described by ( 7) where D; and D, are the respective pore diffusivities in interstitial and surface water, s; and s, are the respective porosities available for diffusion in interstitial and surface water, and 'IC; and 'IC, are the respective ionic concentration gradients in interstitial and surface water. Assuming ( 8) where kd is the distribution coefficient, ()the fraction of surface water available for diffusion, and Pc the clay dry density, Eq.…”
Section: Diffusion Mechanism Of Iodide Ion In Compacted Bentonitementioning
confidence: 99%
“…It was indicated that significant constriction and tortuosity were resulted. However, the iodide ion diffusion in the interstitial water at a steady-state flux NA can be described by ( 7) where D; and D, are the respective pore diffusivities in interstitial and surface water, s; and s, are the respective porosities available for diffusion in interstitial and surface water, and 'IC; and 'IC, are the respective ionic concentration gradients in interstitial and surface water. Assuming ( 8) where kd is the distribution coefficient, ()the fraction of surface water available for diffusion, and Pc the clay dry density, Eq.…”
Section: Diffusion Mechanism Of Iodide Ion In Compacted Bentonitementioning
confidence: 99%